Altered feeding patterns in rats exposed to a palatable cafeteria diet: increased snacking and its implications for development of obesity. - Sarah I Martire (Public Library of Science (PLoS), 2013)
Background Rats prefer energy-rich foods over chow and eat them to excess. The pattern of eating elicited by this diet is unknown. We used the behavioral satiety sequence to classify an eating bout as a meal or snack and compared the eating patterns of rats fed an energy rich cafeteria diet or chow. Methods Eight week old male Sprague Dawley rats were exposed to lab chow or an energy-rich cafeteria diet (plus chow) for 16 weeks. After 5, 10 and 15 weeks, home-cage overnight feeding behavior was recorded. Eating followed by grooming then resting or sleeping was classified as a meal; whereas eating not followed by the full sequence was classified as a snack. Numbers of meals and snacks, their duration, and waiting times between feeding bouts were compared between the two conditions. Results Cafeteria-fed rats ate more protein, fat and carbohydrate, consistently ingesting double the energy of chow-fed rats, and were significantly heavier by week 4. Cafeteria-fed rats tended to take multiple snacks between meals and ate fewer meals than chow-fed rats. They also ate more snacks at 5 weeks, were less effective at compensating for snacking by reducing meals, and the number of snacks in the majority of the cafeteria-fed rats was positively related to terminal body weights. Conclusions Exposure to a palatable diet had long-term effects on feeding patterns. Rats became overweight because they initially ate more frequently and ultimately ate more of foods with higher energy density. The early increased snacking in young cafeteria-fed rats may represent the establishment of eating habits that promote weight gain.